Electrifying Rural Tanzania. A Grid Extension and Reliability Improvement Intervention - Gunther Bensch; Willem Cornelissen; Jor̈g Peters; Natascha Wagner; Jan Reichert; Vendula Stepanikova (The Hague : Netherlands Enterprise Agency, 2019)
This report presents the results of an impact evaluation and institutional analysis of the Electrifying Rural Tanzania project, which was financed through the Dutch Facility for Infrastructure Development ORIO, with co-funding by the Tanzanian government. The project addressed both low rural electrification rates and issues with urban electricity service quality in three target regions in northern and western Tanzania. The evaluation is based on a series of fieldwork activities, including baseline and follow-up surveys in 100 rural communities and three towns in 2014/15 and 2018/19. The analysis relies on a mix of methods to determine project impacts, with the quantitative part primarily using an econometric difference-in-differences approach. One of the most striking findings depicted in the report is the massive rise of solar panel use among households in both off-grid and grid-connected rural communities. As a consequence, increases in electricity source penetration rates were similar in both types of communities. This implies that impacts of the electrification intervention were rather limited to qualitative differences between grid power and off-grid solar electricity. The report also portrays a mixed picture in terms of changes in urban electricity service reliability from the rehabilitation activities supported by the project. – – Dieser Bericht stellt die Ergebnisse einer Wirkungsevaluierung und institutionellen Analyse des Projekts "Electrifying Rural Tanzania" vor, das über die niederländische Infrastrukturentwicklungsfazilität ORIO finanziert und von der tansanischen Regierung mitfinanziert wurde. Das Projekt zielte auf eine Verbesserung sowohl der ländlichen Elektrifizierungsraten als auch der Qualität der städtischen Stromversorgung in drei Zielregionen im Norden und Westen Tansanias ab. Die Evaluierung basiert auf einer Reihe von Datenerhebungsaktivitäten, darunter Baseline- und Folgeuntersuchungen in 100 ländlichen Dörfern und drei Städten in den Jahren 2014/15 und 2018/19. Die Analyse stützt sich auf einen Methodenmix zur Bestimmung der Projektwirkungen, wobei im quantitativen Teil in erster Linie ein ökonometrischer Differenz-in-Differenzen-Ansatz genutzt wird. Eines der auffälligsten Studienergebnisse ist der massive Anstieg der Nutzung von Solarpaneelen in Haushalten sowohl in netzfernen als auch in netzverbundenen ländlichen Dörfern. Infolgedessen verzeichneten beide Dorftypen einen ähnlichen Anstieg in der Verfügbarkeit von Strom. Dies bedeutet, dass die Wirkungen der Elektrifizierungsmaßnahme sich vornehmlich auf qualitative Unterschiede zwischen der Stromversorgung durch Netzstrom und netzunabhängigen Solarstrom beschränkten. Der Bericht zeichnet gleichsam ein gemischtes Bild hinsichtlich der Veränderungen in der Zuverlässigkeit der städtischen Elektrizitätsversorgung durch die vom Projekt unterstützten Rehabilitierungsmaßnahmen.
Keywords: 300; Electricity access; grid reliability; off-grid solar; willingness to pay; impact evaluation